Optical recording reveals topological distribution of functionally classified colorectal afferent neurons in intact lumbosacral DRG. Issue 9 (13th May 2019) - Guo, Tiantian; Bian, Zichao; Trocki, Kyle; Chen, Longtu; Zheng, Guoan; Feng, Bin
Abstract: Neuromodulation as a non‐drug alternative for managing visceral pain in irritable bowel syndrome (IBS) may target sensitized afferents of distal colon and rectum (colorectum), especially their somata in the dorsal root ganglion (DRG). Developing selective DRG stimulation to manage visceral pain requires knowledge of the topological distribution of colorectal afferent somata which are sparsely distributed in the DRG. Here, we implemented GCaMP6f to conduct high‐throughput optical recordings of colorectal afferent activities in lumbosacral DRG, that is, optical electrophysiology. Using a mouse ex vivo preparation with distal colorectum and L5‐S1 DRG in continuity, we recorded 791 colorectal afferents' responses to graded colorectal distension (15, 30, 40, and 60 mmHg) and/or luminal shear flow (20–30 mL/min), then functionally classified them into four mechanosensitive classes, and determined the topological distribution of their somata in the DRG. Of the 791 colorectal afferents, 90.8% were in the L6 DRG, 8.3% in the S1 DRG, and only 0.9% in the L5 DRG. L6 afferents had all four classes: 29% mucosal, 18.4% muscular‐mucosal, 34% low‐threshold (LT) muscular, and 18.2% high‐threshold (HT) muscular afferents. S1 afferents only had three classes: 19.7% mucosal, 34.8% LT muscular, and 45.5% HT muscular afferents. All seven L5 afferents were HT muscular. In L6 DRG, somata of HT muscular afferents were clustered in the caudal region whereas somata of the other classes did not cluster in specific regions. Outcomes of this study can directly inform the design and improvement of next‐generation neuromodulation devices that target the DRG to alleviate visceral pain in IBS patients. Abstract : By establishing a novel optical approach to determine neural activities with single‐spike resolution via GCaMP6f, the current study characterizes the neural encoding from hundreds of colorectal afferents ( 800) in the DRG, which are sparsely distributed and difficult to be recorded with conventional methods High‐threshold muscular afferents, that is, putative colorectal nociceptors are clustered in the caudal region of the L6 DRG, which informs the spatially selective neuromodulation of colorectal nociceptors for better management of visceral pain.